(untitled) (Intent Research Scientific Journal, 2023)
The content of the topic of this article is to show and prove one of the solutions to create many profitable jobs for the population, to completely eliminate poverty, by using land, water and sunlight, contributing to clean air. , is to prove the practical mechanisms of implementing this solution.